Effect of Chicken Manure and Magnesium on the Growth of Arabica Coffee (Coffea arabica L.) Sigararutang - Siahaan, Lasminar; Siregar, Rolan; Nainggolan, Theodora MV; Oppusunggu, Lastayati (Indonesian Journal of Agriculture and Environmental Analytics, 2025)
Effect of Chicken Manure and Magnesium on the Growth of Sigararutang Arabica Coffee. The purpose of the study was to determine the effect of chicken manure and magnesium on the growth of sigararutang arabica coffee. The research was conducted on the land of Fak. Unita Agriculture, with an altitude of ± 1400 m above sea level. Factorial Randomized Group Design (RAK), namely 4 levels of chicken manure K0 (control), K1 (1 kg plot), K2 (3 kg plot), K3 (5 kg plot) and 4 levels of magnesium M0 (control), M1 (10 g/ltr water), M2 (20 g/ltr water), M3 (30 g/ltr water). Parameters observed were plant height increase (cm), stem diameter (mm), leaf area (cm2), number of primary branches (branches) and leaf magnesium nutrient content (%). Treatments were tested with Anova on the observed parameters and continued with DMRT at 5% level and regression test. The results showed that chicken manure treatment had a significant effect on the increase in plant height (cm), stem diameter (mm), number of primary branches (branches) and leaf area (cm2). The treatment interaction significantly affected the number of primary branches (branches), leaf area (cm2) and leaf magnesium nutrient content (%). The treatment of chicken manure at the level of 5 kg/plot had the highest results on the increase in plant height, number of primary branches, leaf area. The interaction of 5 kg/plot chicken manure and 30 g/ltr water magnesium treatment resulted in the highest number of primary branches and leaf area.